Small regions as key sources of traditional knowledge: a quantitative ethnobotanical survey in the central Balkans - Pedja Janaćković; Milan Gavrilović; Milica Miletić; Maja Radulović; Stefan Kolašinac; Zora Dajić Stevanović (BMC, 2022)
Abstract Background Starting from the idea that unexplored areas may yield new and different ethnobotanical information, we performed a survey of traditional uses of plants in two neighboring districts situated in east Serbia (Bor and Aleksinac), both lacking in previous ethnobotanical reports, but characterized by an interesting history and culture, together with some specific features. In this study, we hypothesized that such small and specific areas could be of high ethnobotanical importance. Methods Semi-structured interviews were used with 155 informants. Relative cultural importance (RCI) indices, such as the frequency of citation (FC), relative frequency of citation (RFC), relative importance index (RI), informant consensus factor (ICF-FIC), use value (UV), fidelity level (FL) and Jaccard index (JI), were calculated, and principal coordinate analysis (PCoA) was performed. Results In this study, 2333 use-reports and 114 plants were recorded. Of the 101 medical herbs, 33 are included in the European Pharmacopoeia Edition 8.0. The most frequently used mode of preparation was as an infusion (50.0%), while leaf (44.7%) was the most used plant part. The highest FC and RFC values were recorded for Hypericum perforatum L. (13.1 and 0.2, respectively), while the highest RI was documented for Urtica dioica L. (1.0). ICF and FL indices showed important differences among selected groups of informants. The PCoA showed three homogeneous plant groups. Plants were mostly used for the treatment of digestive (49.1%), circulatory (41.2%) and respiratory system disorders (35.1%). Thirty-seven (32.5%) herbs were used for human nutrition, 14 (12.3%) in veterinary medicine, 17 (14.9%) in rituals and ethnoculture, while 24 (21.0%) for miscellaneous purposes. The highest degree of similarity was determined with studies conducted in close proximity. Four species are new to Balkan ethnobotany. New uses for some well-known plants are highlighted. Conclusion The study indicated that small and specific areas in the Balkans may be an important reservoir of ethnobotanical knowledge.